Endometriosis in Postmenopausal Woman Without Previous Hormonal Therapy: A Case Report - Mine İslimye Taşkın; Meltem Çağrı Menteşe; Engin Uzgören; Ümit İnceboz (Gynecology Obstetrics & Reproductive Medicine)
Endometriosis is a benign, estrogen-dependent, chronic gynecological disorder commonly associated with pelvic pain and infertility. The prevalence of pelvic endometriosis is high, affecting approximately 6- 10% of women of reproductive age. Although endometriosis has been associated with the occurence of menstrual cycles, it may affect between 2-5% of postmenopausal women. In this presentation, we would like to draw attention to such cases of postmenopausal endometriosis.